(untitled) (Al-Academy, 2024)
The current research aims to build an educational design according to the Roberts model to develop creative thinking and performance skills among students of the Institute of Fine Arts in the subject of interior design. To achieve the research objectives, the researcher developed (6) null hypotheses, so the research population was determined by the students of the Institute of Fine Arts, which numbered (86) male and female students specializing in interior design taught in (4) institutes. After that, a purposive sample was chosen, which was represented by students of the Institute of Fine Arts for girls, the number of whom was (14) female students were distributed into two groups, with (7) female students for each group. As for the research procedures, an educational model was designed according to the Roberts educational model, which consists of (4) main clusters and branches from the first cluster (15) steps. Two types of tests were also designed, the first related to measuring creative thinking and the second related to measuring cognitive achievement. And skill performance in the interior design subject. These tools were presented to a group of arbitrators to show the reliability coefficient for each test, and then they were applied to a pilot sample in order to show the reliability coefficient. After that, these tests were used to obtain the results expected from their application to the basic research sample. As for the research procedures, an educational model was designed according to the (Roberts) educational model, which consists of (4) main clusters and branches from the first cluster (15) steps. Two types of tests were designed, including a measure of creative thinking and a measure of cognitive achievement and skill performance in the subject of design. The procedure was presented to a group of experts to verify its validity in order to measure the objectives that were developed to measure it and were applied to the basic research sample. To show the results, the researcher used a set of statistical methods (Mann-Whitney, Wilcoxon test, coefficient of difficulty and discrimination, and the Keuder-Richadson/20 equation) for reliability. Through the results of the current research, which showed that the students of the experimental group who studied the subject according to the educational design outperformed the control group who studied the subject according to the usual method, it indicated that there was a statistically significant difference in favor of the educational design that was built by the researcher according to the steps of the Roberts model. ) in developing creative thinking and performance skills among students of the Institute of Fine Arts in the subject of interior design. The reason for the excellence is due to the following reasons: - Presenting the educational design according to the Roberts model gives the student the opportunity to interact with the educational material, which helps him think creatively and develops his performance skills. Through her teaching to the experimental group through the educational model according to the (Roberts) model, the researcher sensed the emergence of enthusiasm and activity among the students by following the steps of the educational units that were accepted by them, and this indicates the validity of the educational units prepared by the researcher.